PENDAMPINGAN PASTORAL DALAM GEREJA KATOLIK: PERAN KATEKIS DALAM MEWUJUDKAN EVANGELISASI DAN FORMASI IMAN YANG BERKELANJUTAN - Yohanes Chandra Kurnia Saputra (Jurnal Pelayanan Pastoral, 2025)
Pastoral accompaniment in the Catholic Church plays a crucial role in shaping the faith of the faithful continuously, yet its implementation still faces various challenges. While many studies discuss the role of catechists in evangelization and catechesis, research on concrete strategies for effective pastoral accompaniment remains limited. This article aims to analyze the role of catechists in supporting evangelization and faith formation, as well as identify effective pastoral accompaniment strategies by integrating teachings from the Holy Scripture and Church documents. The method used in this research is literature review, examining various written sources including the Holy Scripture, Church documents, and previous studies relevant to the topic of pastoral accompaniment. The theoretical framework includes pastoral principles found in the Holy Scripture and key teachings from Church documents such as Evangelii Nuntiandi and Catechesi Tradendae. The data analysis technique used is thematic analysis, which involves tracing and grouping the main themes from various literature sources to understand the relationships between concepts. The findings show that community-based pastoral accompaniment and the use of digital technology can enhance the effectiveness of pastoral programs. Challenges include limited resources and resistance to change, but there are significant opportunities for program development through social and ecological synergy. In conclusion, the role of catechists is vital in realizing evangelization and continuous faith formation, with innovative and adaptive approaches to the evolving times. Effective pastoral accompaniment can help build a strong and relevant Church for the future.